Demographics of colonic health: Unveiling sex- and age-driven trends in a cross-sectional retrospective analysis of 2523 colonoscopy procedures - Arwa F Flemban; Saeed M Kabrah; Mohammad Aldabagh; Hanan M Abd Elmoneim; Samah Alharbi (Journal of International Medical Research)
Background Colonic abnormalities, ranging from benign haemorrhoids to malignancies, pose a significant global health burden. Despite extensive research in Western populations, regional data from Saudi Arabia remain limited. Objective To evaluate the prevalence, demographic trends and clinical relevance of colonic abnormalities in a Saudi Arabian population. Methods This retrospective cross-sectional study analysed 2523 colonoscopy reports from Al Noor Specialist Hospital, Makkah, Saudi Arabia, between 1 March 2010 and 30 December 2020. Reports were examined for key findings, including polyps, tumours, bleeding, diverticulosis, haemorrhoids and inflammation. Statistical analyses were used to assess age- and sex-specific trends. Results Haemorrhoids (38.1%) and polyps (12.2%) were the most frequent abnormalities. Polyps were most common in patients aged 50–59 years. Sex differences were significant; men showed a higher prevalence of haemorrhoids ( p  < 0.001) and active bleeding ( p =  0.04), while women exhibited a higher prevalence of ulcers and erosions ( p  < 0.001). Older patients exhibited a higher prevalence of diverticular disease and bleeding; younger individuals (20–39 years) had higher rates of inflammatory changes. Conclusion Colonic abnormalities were prevalent in this Saudi population, with distinct age- and sex-specific patterns. These findings support the need for tailored screening strategies. Future multicentre studies should explore the effect of genetic, dietary and environmental factors on colonic health in the study region.